Maturity Evaluation of Information Technology Governance at PT Insurance XXX Using the DSS02 and DSS03 domain Cobit 5 Framework - Cahyono Budy Santoso (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
PT Asuransi XXX is one of the largest national general insurance companies in Indonesia, which since its inception was focused on the oil and gas industry. As time goes by and the development of the business world, XXX insurance company responds to market challenges by expanding its business to segments outside the oil and gas industry, including aviation, chemical & petrochemical, power generation, mining and manufacturing, both conventional and sharia-based businesses. Supporters of the company's operational development have implemented a reliable application system. In its development, this system needs to be managed for service request management, incidents and management, because this system is getting bigger, more complex and the number of users is increasing. To measure however great the quality of service, ongoing information is needed an audit method that can measure whether the services provided have been running well, effectively and efficiently. COBIT 5.0 DSS02 and DSS03 domains are used as methods to measure whether the level of IT service demand management capabilities, incidents in managing problems with the system, has been running effectively and optimally. From the measurement results of all these processes, it can be seen that the DSS02 and DSS03 levels are at level 2 (managed).